Analisis Ayat-Ayat Pendidikan Tentang Pembentukan Karakter Peserta Didik (Objek Pendidikan) - Lestari, Ayu; Sarah, Elvita; Massaid, Fajri; Amanda, Amanda; Wismanto, Wismanto (Faidatuna, 2024)
The Koran has explained how important education is which is very influential in the lives of shaping the character of students to become Muslims with noble morals, especially in the field of developing religious education which is used as a basis for learning both in terms of formal, informal and non-formal institutions which have a very important role in it. The aim of this research is to develop and foster an academic culture in the school environment. Where schools can improve learning and education effectively and sustainably. The method used in this research uses a qualitative approach, with a research design (research library) sourced from books, the latest journals and other sources of information as well as those that support the writing of this article, for example trusted national newspapers. The results of the research in this discussion show that based on the explanation of the Al-Quran verses that have been explained in Q.S At-Taubah 9/122 and Q.S An-Nisa 4/170 regarding forms of classification regarding students and of course they have given meaning to the subjects and objects that The most important thing in education is students, where they are always prioritized to gain an understanding of learning and character formation, this cannot be separated from the role of an educator who always directs students to become human beings who are not only intellectual in general knowledge but also intelligent in developing their morals.